Spectrophotometric Method for Estimation of Atenolol in Tablet Dosage Form - Kumar, B.; Patel, R.; Bhandari, A. (Asian Journal of Chemistry, 2010)
A simple and accurate spectrophotometric method has been developed for the quantitative estimation of atenolol in bulk and tablets. The method is based upon the reaction of atenolol with 1-chloro-2,4-dinitrobenzene, forming a complex, which is spectrophotometrically analyzed. The absorbance maxima (λmax) was found to be 224.6 nm. Optimization of reaction was carried out with the factors: temperature, time, stability of complex, molar ratio of drug : reagent. The proposed method was validated as per ICH guidelines. The recovery studies confirmed the accuracy and precision of the method.